Gender Equality in the New Millennium: Goal or Gimmick? - ANTROBUS, PEGGY (Caribbean Quarterly, 2006)
At the Millennium Summit in September 2000 the largest gathering of world leaders adopted the UN Millennium Declaration, committing their nations to a new global partnership to reduce extreme poverty and setting out a series of time-bound targets, all with a deadline of 2015, that have become known as the Millennium Development Goals (MDGs). The Millenium Development Goals are now part of an international development framework which many countries in the Caribbean have signed on to. This paper addresses the question of how the Millenium Development Goals can be made to work to promote gender equality and empowerment in the Caribbean Community (CARICOM) region. The analysis here will not be limited to "gender equality and women's empowerment (MDG Goal 3). It will also highlight the gender dimensions of some of the other MDGs that closely related to women's equality and empowerment - as a means and as an outcome. Finally, the analysis and suggestions in relation to strategies "to ensure that gender inequalities are identified and addressed in the MDG monitoring process and in national policy responses from governments" will focus on Caribbean realities. Suggestions are made by drawing on the findings and insights on the linkages between global trends, development strategies (including the macroeconomic policy framework of structural adjustment) and their impact on poor women, and the ways in which we might now approach activist interventions toward the goal of gender equality and women's empowerment.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; caraïbes; cours; discipline; féminisme des caraïbes; féminismes noirs; histoire et politique; pol4022; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences de l'éducation; thématiques

Governing women's morality: a study of Islamic veiling in Canada - Atasoy, Y. (EUROPEAN JOURNAL OF CULTURAL STUDIES, 2006)
The veiling of Muslim women is subject to strongly contested ideas about whether the veil is a symbol of women's subordination to an oppressive tradition or a means of emancipation from that tradition. This article suggests that women's own personal reasons for veiling must be analysed. Data collected from published documents from Muslim organizations allows for demonstration that the veil is configured as central to an Islamic moral code of female modesty. A further analysis of findings from interviews conducted with veiled Muslim women in Winnipeg shows the nuanced ways in which women enact this code.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; corps; cours; discipline; féminisme islamique; histoire et politique; identité; manitoba; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; winnipeg

Erika Mann et Pauline Julien : voix parallèles dans l'exil et l'engagement - Augustin, Myriam (Université McGill, 2006)
Le présent mémoire de maîtrise se concentre sur deux artistes, l'Allemande Erika Mann (1905-1969) et la Québécoise Pauline Julien (1928-1998). Seront examinés l'impact de leur contribution artistique, provenant en partie de leur phase respective d'exil auto-administré, ainsi que leur engagement politique. Les aspects biographiques et socio-historiques sont abordés puisqu'ayant eu une influence sur la vie et la carrière de chacune des deux artistes. Des textes écrits ou interprétés par elles seront analysés. Enfin, des pistes comparatives seront établies, démontrant les nombreux parallèles dans leur vie professionnelle et artistique respective.
Keywords: 1900-1999; allemagne; amériques; arts; discipline; europe; femmes* artistes; histoire et politique; militance; mémoires/thèses; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; états-unis; études littéraires

In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

Y-a-t-il une troisième vague féministe? - Lamoureux, Diane (Cahiers du Genre, 2006)
Malgré un certain scepticisme face à la notion de troisième vague, utilisée aux États-Unis pour caractériser celles qui sont arrivées au féminisme dans les années 1990, il me semble intéressant d’examiner comment les jeunes féministes définissent leurs enjeux et leur rapport à celles qui les ont précédées. Il s’agit donc, d’une part, de montrer comment se développe un féminisme du « post » — postmoderne, postcolonial mais aussi postféministe. D’autre part, il sera question du « tri » effectué par rapport à l’héritage de la vague féministe de la fin des années 1960. Cela débouchera sur une caractérisation de cette troisième vague féministe.
Keywords: 1900-1999; amériques; cours; fem1000; histoire et politique; mouvements féministes; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; transfert des connaissances; états-unis

Aspiration, reunification and gender transformation in Jat Sikh marriages from India to Canada - MOONEY, NICOLA (Global Networks, 2006)
In this article I explore marriage as a strategy of family migration among a transnational community of middle-class Jat Sikhs. Family reunification and status aspirations are examined as central concerns of the transnational movement of Jat Sikhs from India to Canada. It is argued that Jat Sikh transnationalism and gender are mutually-constitutive: migration strategies can construct women, as well as men, as agents of marital citizenship, and in facilitating migration, transnational marriage may transform practices and notions of gender and status. The article is based on preliminary ethnographic research among Jat Sikh brides in Toronto and Vancouver, and forms part of a larger study of gender, modernity and identity in Indo-Canadian Jat Sikh marriages.
Keywords: amériques; anthropologie; approches et analyses; asie; canada; colombie-britannique; cours; discipline; famille; histoire et politique; inde; intersectionnalité; justice sociale; mariage; mariages transnationaux; migration; ontario; premier cycle; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; toronto; vancouver

Arab American Femininities: Beyond Arab Virgin/ American(ized) Whore - Naber, Nadine (Feminist Studies, 2006)
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; anthropologie culturelle; approches et analyses; arabes-américaines; cours; discipline; discours dominant; femmes* arabes; féminisme islamique; histoire et politique; identités culturelles; intersectionnalité; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sex2283; système colonial; systèmes d'oppressions; thématiques; états-unis

Gone ‘underground’? Lesbian visibility and the consolidation of queer space in Montréal - Podmore, Julie A. (Social & Cultural Geography, 2006)
Pendant les deux dernières décennies, les chercheur.e.s en études urbaines ont abordé la question du rôle de l'appartenance sexuelle dans les géographies gais et lesbiennes dans les grandes villes postindustrielles. Ces études montrent que si les hommes gais ont souvent produit des territoires distincts et fermés dans les quartiers centraux urbains, les formes que prennent l'emprise territoriale lesbienne à l'échelle urbaine sont demeurées relativement «invisibles» du fait que leurs communautés sont conçues à partir de réseaux sociaux et non de zones commerciales. Une comparaison de la manière dont ces deux populations ont évolué dans les quartiers centraux urbains des villes postindustrielles durant les années 1990 «queer» permet de constater l'existence d'un clivage lié au sexe et d'une interprétation historique particulière de leur évolution territoriale et de leur visibilité qui pourraient se démarquer de manière significative de celles des années précédentes. Cet article présente donc un aperçu historique sur une longue période de la géographie des lesbiennes dans une agglomération urbaine importante à partir d'une étude de cas sur l'univers des bars de lesbiennes depuis 1950. L'étude porte tout particulièrement sur les conditions préalables au développement d'une zone commerciale lesbienne dans la ville au cours des années 1980, et sur les facteurs ayant contribué à son déclin au cours des années 1990. Cette étude de cas décrit sommairement le caractère changeant des pratiques territoriales lesbiennes à l'échelle urbaine de Montréal depuis 1950. Elle montre que la territorialité et la visibilité des lesbiennes à Montréal ont été grandement influencées par les dynamiques locales à l'échelle des quartiers, les idéologies internes et les rapports politiques et spatiaux avec les hommes gais. En dernière analyse, ces constats suggèrent qu'aujourd'hui la visibilité lesbienne à l'échelle urbaine a peut-être été affaiblie par l'identification de plus en plus importante avec les formes communautaires «queer» et de leur ancrage territoriale dans le village gai de Montréal.
Keywords: amériques; design; discipline; histoire et politique; identités LGBTQIA2+; occupation de l'espace; personnes gay; personnes lesbiennes; québec; ressource en ligne; régions géographiques; thématiques; urbanisme

Radical gestures: feminism and performance art in North America - Wark, Jayne (McGill-Queen's University Press, 2006)
Wark brings together a wide range of artists, including Lisa Steele, Martha Rosler, Lynda Benglis, Gillian Collyer, Margaret Dragu, and Sylvie Tourangeau, and provides detailed readings and viewings of individual pieces, many of which have not been studied in detail before. She reassesses assumptions about the generational and thematic characteristics of feminist art, placing feminist performance within the wider context of minimalism, conceptualism, land art, and happenings
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; art contemporain; art féministe; arts; corps; cours; discipline; femmes* artistes; féminisme pop; har4600; histoire de l'art; histoire et politique; militance; performance; premier cycle; périodes historiques; régions géographiques; thématiques